Association of vancomycin serum concentrations with efficacy in patients with MRSA infections: a systematic review and meta-analysis. (July 2015) - Steinmetz, T.; Eliakim-Raz, N.; Goldberg, E.; Leibovici, L.; Yahav, D.
Abstract: Recent Infectious Diseases Society of America guidelines for the treatment of methicillin-resistant Staphylococcus aureus (MRSA) infections recommend maintaining vancomycin trough concentrations of 15–20 mg/L for serious infections. We conducted a systematic review and meta-analysis of all studies assessing the impact of low (<15 mg/L) vs. high (≥15 mg/L) vancomycin trough level on the efficacy of MRSA infections treatment. Four prospective and 12 retrospective studies were included (2003 participants). No significant difference was demonstrated between low and high vancomycin trough level for the outcome of all-cause mortality (odds ratio (OR) 1.07, 95% confidence interval (CI) 0.78–1.46, I 2  = 28%). In studies evaluating mainly MRSA pneumonia, there was significantly higher mortality with low vancomycin level (OR 1.78, 95% CI 1.11–2.84). No significant difference was demonstrated in treatment failure rates (OR 1.25, 95% CI 0.88–1.78, I 2  = 51%). However, excluding one outlier study from the analysis, treatment failure became significantly higher in patients with low vancomycin trough level (OR 1.46, 95% CI 1.12–1.91, I 2  = 16%). Microbiologic failure rates were significantly higher in patients with low vancomycin levels (OR 1.56, 95% CI 1.08–2.26, I 2  = 0%). Nephrotoxicity was significantly higher with vancomycin levels of ≥15 mg/L. However, no cases of irreversible renal damage were reported. Current data on the effectiveness of higher vancomycin trough levels in the treatment of MRSA infections are limited to few prospective and mainly retrospective studies. Our findings support the current recommendations for maintaining vancomycin trough levels of ≥15 mg/L in the treatment of severe MRSA infections, although no difference in all-cause mortality was observed.